The κ–μ Shadowed Fading Model: Unifying the κ–μ and η–μ Distributions - Moreno-Pozas, Laureano; López-Martínez, Francisco Javier; París-Ángel, José Francisco; Martos-Naya, Eduardo (IEEE Transactions on Vehicular Technology, 2016)
This paper shows that the recently proposed k-μ shadowed fading model includes, besides the k-μ model, the η-μ fading model as a particular case. This has important relevance in practice, as it allows for the unification of these popular fading distributions through a more general, yet equally tractable, model. The convenience of new underlying physical models is discussed. Then, we derive simple and novel closed-form expressions for the asymptotic ergodic capacity in k-μ shadowed fading channels, which illustrate the effects of the different fading parameters on the system performance. By exploiting the unification here unveiled, the asymptotic capacity expressions for the k-μ, η-μ, and Rician shadowed fading models are also obtained in closed form as special cases.
Keywords: I; Random variables; Shadow mapping; Rayleigh channels; Rician channels; Signal to noise ratio; Shape